Images of psychiatry and psychiatrists. (January 2015) - Stuart, H.; Sartorius, N.; Liinamaa, T.; the Images Study Group
<x xml:space="preserve">Abstract</x> Objective This study surveyed medical teaching faculty to determine their attitudes toward psychiatry and psychiatrists. Method We conducted a multisite survey of a probability sample of 1057 teaching medical faculty members from 15 academic teaching centers in the United Kingdom, Europe, and Asia stratified by early, middle, and late career stage. The average response rate across countries was 65%. Results The outstanding findings were that 90% of respondents considered that psychiatrists were not good role models for medical students, 84% thought psychiatric patients were unsuitable to be treated outside of specialized facilities, and 73% thought psychiatric patients were emotionally draining. We noted statistically significant differences by country, gender, career stage, and specialty. Conclusion These results highlight why recruitment into psychiatry is problematic in many countries and suggest that greater attention should be given to improving the perception of psychiatrists as good role models and the efficacy of psychiatric treatments.